2015
DOI: 10.1002/ijc.29927
|View full text |Cite
|
Sign up to set email alerts
|

Blocking mammalian target of rapamycin alleviates bone cancer pain and morphine tolerance via µ‐opioid receptor

Abstract: The current study was to examine the underlying mechanisms responsible for the role of mammalian target of rapamycin (mTOR) in regulating bone cancer-evoked pain and the tolerance of systemic morphine. Breast sarcocarcinoma Walker 256 cells were implanted into the tibia bone cavity of rats and this evoked significant mechanical and thermal hyperalgesia. Our results showed that the protein expression of p-mTOR, mTOR-mediated phosphorylation of 4E-binding protein 4 (4E-BP1), p70 ribosomal S6 protein kinase 1 (S6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Local perfusion of rapamycin into the spinal cord attenuates formalin-induced neuronal hyperexcitability in the dorsal horn_ENREF_6 [11]. Note that rapamycin attenuates pain response and this is accompanied with downregulated mTOR, S6K1 and 4E-BP1 [12]. These findings indicate that mTOR and its downstream signals are activated under persistent pain conditions and contribute to the development of spinal pain sensitization.…”
Section: Hushan Wangmentioning
confidence: 67%
See 1 more Smart Citation
“…Local perfusion of rapamycin into the spinal cord attenuates formalin-induced neuronal hyperexcitability in the dorsal horn_ENREF_6 [11]. Note that rapamycin attenuates pain response and this is accompanied with downregulated mTOR, S6K1 and 4E-BP1 [12]. These findings indicate that mTOR and its downstream signals are activated under persistent pain conditions and contribute to the development of spinal pain sensitization.…”
Section: Hushan Wangmentioning
confidence: 67%
“…An infusion pump was used to deliver vehicle and drugs and the pump was set to constantly over a period of 60 min. Note that a prior study [12] using the same approach to intrathecally infuse rapamycin (1, 5 and 10µg) and LY294002 (1, 5 and 10µM). It was shown that 10µg of rapamycin and 10µM of LY294002 were effective to attenuate mechanical and thermal hyperalgesia.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…It was demonstrated that p70s6k activation by neuropeptide Y or cysteine-rich, angiogenic inducer 61, promoted eNOS phosphorylation in endothelial cells and led to blood vessel relaxation (Cheng et al, 2012;Hwang et al, 2015). Moreover, two other studies showed that increased p70s6k1 phosphorylation facilitated PKA expression and enhanced its activity in tissues (Soulard et al, 2010;Jiang et al, 2016). Taken together, it is very likely that TXL can reduce MIRI via the p70s6k1/PKA/eNOS pathway, but further studies will be needed to confirm this speculation.…”
Section: Discussionmentioning
confidence: 97%
“…Decreased D-serine levels have previously been associated with attenuation of morphine tolerance [34,35]. However, in other studies, activation of the mTOR pathway has been linked to the development of opioid tolerance and hyperalgesia [36,37]. Interestingly, a7-nACh receptor agonists have shown efficacy in pre-clinical models of neuropathic pain [38,39] and remifentanil-induced hyperalgesia [40] by reducing the release of glial pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%